Harmonizacja prawa ukraińskiego z systemem rynku wewnętrznego UE na podstawie układu stowarzyszeniowego - Cieśliński, Aleksander (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
This article is part of a bigger paper that was published in the previous volume and the current one. Its purpose is to analyze the current situation of Ukraine after entering into force of the association agreement. The idea of its author is to juxtapose the legal system of EU single internal market and its rules with the set of obligations regarding introduction of free movement of goods, persons, services and capital in the coming years stemming from this agreement. The reason to concentrate on this particular part of EU-Ukraine relations is the fundamental meaning of the above rules both for the modernization and future development of Ukraine and its future capability to apply for real membership. In order to evaluate this, the first article analyzed the legal construction of the association agreement itself. The second one is concerned with the convergence between the regulatory frameworks of Ukraine and the EU seen as a way to its integration into the European economic legal space.
Keywords: association agreement; Ukraine-EU; single internal market; harmonization